Moral Crusade Oleh Slank Sebagai Reaksi Sosial Terhadap Penyalahgunaan Narkoba - Intan Rafika Sabrina (Jurnal Kriminologi Indonesia, 2017)
This thesis is written with the purpose of widening the study of moral crusade done by musical groups as a form of informal social reaction on the issue of drugs and its abuse. The author sees that the effort of preventing drugs abuse can also be done not only by the government but also musical groups as public figures. In this case, musical groups act as the agents of change on the dynamic social condition. The social bond and admiration shared by both the musical groups and their fans are utilized to prevent the practice of drugs abuse. The music itself and the theatrical acts on the stage act as the media to spread the message of anti-drugs abuse. Secondary sources such as news, scientific journals and articles, official survey reports along with documents published by related institutions become the basis of the analysis used in this thesis. Based on those sources, the author found that there is a correlation between moral crusade, that acts as a form of social reaction on criminal acts with the purpose of realizing a social change; and the birth of social movement within the society. Keywords : music group, informal social reaction, drugs abuse, social bond, moral crusade, change agent, social change, social movement